Toba-Bataknese Interjection Ale!: A Natural Semantic Metalanguage Approach - Viqa Sari, Wina; Mulyadi (TALENTA, 2024)
Interjections are words used to express emotions or spontaneous reactions. There are various interjections in the Batak Toba language, but the one discussed in this article is the interjection